1999
DOI: 10.1073/pnas.96.4.1333
|View full text |Cite
|
Sign up to set email alerts
|

The neurotransmitter receptor-anchoring protein gephyrin reconstitutes molybdenum cofactor biosynthesis in bacteria, plants, and mammalian cells

Abstract: The molybdenum cofactor (Moco), a highly conserved pterin compound complexing molybdenum, is required for the enzymatic activities of all molybdenum enzymes except nitrogenase. Moco is synthesized by a unique and evolutionarily old pathway that requires the activities of at least six gene products. Some of the proteins involved in bacterial, plant, and invertebrate Moco biosynthesis show striking homologies to the primary structure of gephyrin, a polypeptide required for the clustering of inhibitory glycine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
116
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 42 publications
0
116
1
1
Order By: Relevance
“…Indeed, GPHN expression is not restricted to rat brain and spinal cord but is also found in liver, kidney, lung, and retina (28 -30). Gephyrin knock-out mice and reconstitutive cell culture assays have demonstrated that gephyrin expression in nonneuronal tissue is a requirement for the biosynthesis of molybdenum cofactor (20,31). Striking homologies are observed between the primary structure of GPHN and proteins involved in bacterial, plant, and invertebrate molybdenum cofactor biosynthesis.…”
Section: Gephyrin (Gphn) Is An Organizational Protein That Clusters Amentioning
confidence: 98%
“…Indeed, GPHN expression is not restricted to rat brain and spinal cord but is also found in liver, kidney, lung, and retina (28 -30). Gephyrin knock-out mice and reconstitutive cell culture assays have demonstrated that gephyrin expression in nonneuronal tissue is a requirement for the biosynthesis of molybdenum cofactor (20,31). Striking homologies are observed between the primary structure of GPHN and proteins involved in bacterial, plant, and invertebrate molybdenum cofactor biosynthesis.…”
Section: Gephyrin (Gphn) Is An Organizational Protein That Clusters Amentioning
confidence: 98%
“…Similarly, the MOCS2 locus encodes the two subunits of MPT synthase and has been shown to be bicistronic with overlapping reading frames encoding MOCS2A and MOCS2B, the congeners of E. coli MoaD and MoaE (7). In the last step of Moco biosynthesis in humans, molybdenum is incorporated into MPT by the two-domain protein gephyrin (8,9). Based on the presence or absence of precursor Z in clinical samples, Moco deficiency was originally divided into two complementation groups.…”
mentioning
confidence: 99%
“…Surprisingly, the analysis of gephyrin's primary structure revealed signiWcant sequence homologies of the amino-and carboxy-terminal thirds to proteins involved in the biosynthesis of the molybdenum cofactor (moco) (Prior et al 1992;Stallmeyer et al 1999), a pterin cofactor required for the activity of molybdenum-dependent oxidoreductases, namely sulWte oxidase, xanthine dehydrogenase and aldehyde oxidase all of which are predominantly expressed in liver but also in brain (Mendel and Schwarz 2002;Schwarz and Mendel 2006). The amino terminal part of gephyrin (amino acids 1-181), now called the G-domain, shows homologies to the MogA protein, whereas the carboxy terminal part (amino acids 318-736), now called E-domain, is homologous to the MoeA protein of E. coli.…”
Section: Homologous Proteinsmentioning
confidence: 99%
“…The amino terminal part of gephyrin (amino acids 1-181), now called the G-domain, shows homologies to the MogA protein, whereas the carboxy terminal part (amino acids 318-736), now called E-domain, is homologous to the MoeA protein of E. coli. In plants and invertebrates these two polypeptides were fused to a single protein named cnx1 (Arabidopsis thaliana) and cinnamon (Drosophila melanogaster), respectively (Stallmeyer et al 1999). In vertebrates the two domains with homology to the aforementioned proteins are connected by an extensive central region (C-domain), which does not display homologies to known proteins in the databases (Fig.…”
Section: Homologous Proteinsmentioning
confidence: 99%
See 1 more Smart Citation